Extensive polymorphism in the mitochondrial DNA of apes. - Ferris, S D (1981)
Ape species are 2-10 times more variable than the human species with respect to the nucleotide sequence of mtDNA, even though ape populations have been smaller than the human population for at least 10,000 years. This finding was made by comparing purified mtDNAs from 27 individuals with the aid of 25 restriction endonucleases; for an additional 59 individuals, comparisons were made with fewer enzymes by using the blot hybridization method. The amount of intraspecific sequence divergence was greatest between orangutans of Borneo and Sumatra. Among common chimpanzees, a large component of the variation is due to two highly distinct forms of mtDNA that may reflect a major geographic subdivision. The least amount of sequence variation occurred among lowland gorillas, which exhibit only twice as much sequence variation as humans. The large intraspecific differences among apes, together with the geological and protein evidence, leads us to propose that each ape species is the remnant of an ancient and widespread population that became subdivided geographically and reduced in size and range, perhaps by hominid competition. The low variation among human mtDNAs is consistent with geological evidence that the human species is young. The distribution of site changes within the mitochondrial genome was also examined. Comparison of closely related mtDNAs shows that the ribosomal RNA genes have diverged more slowly than the rest of the genome.